Marketing Srategy of Tempe Crypics to Increase Income for MSME Group in Mulyasari Village, Losari District - Setiawan, Dedy (Green Publisher Indonesia, 2020)
The marketing strategy of the tempe chips MSMEin the village of Mulyasari does not yet have modern marketing skills. This has greatly affected business development, because if rely solely on sales by leaving it in small shops, it is feared that the sustainability of business will be threatened. The purpose of this research is to develop social media such as youtube, instagram, facebook, twitter and whatsaap to increase the income of MSME tempe chips in Mulyasari village. The research method used in this activity is Participatory Action Research. Researchers did social media design, implemented social media, and analyzed MSME tempe chips using existing social media. The results of the study found that the income of these tempe chips MSME obtained an increase of 36.05% from the previous profit. Initially, the monthly income of tempe chips MSME earned around Rp. 1,803,000. However, after using a modern marketing strategy using social media so that the tempe chips MSME business can earn a monthly profit of around Rp. 2. 453,000, then the income of this tempe chips MSME will increase by Rp. 650,000